2003
DOI: 10.1159/000071463
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Neurotoxicity of Toluene: in vivo and in vitro Effects on Astroglial Cells

Abstract: Toluene, an inexpensive and available industrial solvent, has become increasingly popular as a drug of abuse. Inhaling toluene leads to a feeling of euphoria and several reports have shown that children born to women who had abused toluene during pregnancy present a syndrome (toluene embryopathy or fetal solvent syndrome) that is characterized by CNS effects (e.g. microencephaly), growth retardation and facial dysmorphologies. The characteristics of the fetal solvent syndrome are very similar to those observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 26 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…In the present study, we showed that preweaning solvent inhalation of toluene and n ‐hexane (at 75% and 18%, respectively) significantly reduced brain weight and size and considerably impaired dendritic growth and branching in frontal, parietal and occipital pyramidal cells. The solvent‐induced reduction in brain weight and size is consistent with a previous study in which rat pups exposed to toluene between P4 and P10 displayed a dose‐dependent decrease in brain weight and astrocytic markers (Burry et al, 2003). Similarly, intraperitoneal toluene administration to rat pups at P4–P7 significantly reduced brain weight and caused glutamatergic dysfunction and neurobehavioral abnormalities (Chen et al, 2005; Chien et al, 2005).…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, we showed that preweaning solvent inhalation of toluene and n ‐hexane (at 75% and 18%, respectively) significantly reduced brain weight and size and considerably impaired dendritic growth and branching in frontal, parietal and occipital pyramidal cells. The solvent‐induced reduction in brain weight and size is consistent with a previous study in which rat pups exposed to toluene between P4 and P10 displayed a dose‐dependent decrease in brain weight and astrocytic markers (Burry et al, 2003). Similarly, intraperitoneal toluene administration to rat pups at P4–P7 significantly reduced brain weight and caused glutamatergic dysfunction and neurobehavioral abnormalities (Chen et al, 2005; Chien et al, 2005).…”
Section: Methodssupporting
confidence: 91%
“…Animals exposed to toluene during pre‐ or early‐postnatal periods display reductions in brain weight and hippocampal volume as well as delays in neurogenesis, changes to astrocytic markers, and alterations in the expression and function of N ‐methyl‐ d ‐aspartate (NMDA) glutamate receptors (Bowen et al, 2005, 2007; Burry et al, 2003; Gospe and Zhou, 2000; Lee et al, 2005; Slomianka et al, 1990). In previous studies, we have demonstrated that weanling rats exposed to a mixture of solvent vapors commonly found in glues (75% toluene and 18% n ‐hexane) displayed significant morphological impairments in cerebellar Purkinje cells (Pascual et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Of those, only MeHgCl is a true inhibitor of 'Neural Proliferation' in vivo , Burke et al, 2006, whereas the other compounds affect neurodevelopment through different target processes (e.g. Toluene affects astroglial differentiation (Burry et al, 2003) or Manganese alters the dopaminergic system (Tran et al, 2002)). In the 'Positives, negative for this Endpoint' group, 16 different compounds were negative, although a priori classified as 'DNT positive compounds'.…”
Section: Neural Proliferationmentioning
confidence: 99%
“…'True Positives' were identified with stem-/progenitor cells (3) and primary cells (7), 'Positives, negative for this Endpoint' with primary cells (11) and stem-/progenitor cells (3), and the 'True Negatives' were classified correctly only with primary cells (3 ; Table 27). Within the compounds tested for effects on astrocyte endpoints, ethanol and toluene are two DNT compounds affecting astrocyte development in vivo (Burry et al, 2003, Vemuri and Chetty, 2005, Valles et al, 1996. Therefore, an alternative assay used for DNT testing should be able to identify this positive compound correctly as 'True Positive'.…”
Section: Neural Stem-/progenitor Cell Endpointsmentioning
confidence: 99%
“…It has been shown, however, that even sub-chronic toluene exposure can result in cerebellar atrophy (Filley et al, 2004) and deterioration of memory and attention (Lee et al, 2003;Kang et al, 2005). Murine models have revealed that exposure to low levels (40À80 ppm) of toluene results in memory loss and impaired visuospatial learning (Von et al, 1993), damage to neuroglial cells (Burry et al, 2003), and significant and genderdependent alterations in the autonomic nervous system (ANS) related to the rate of catecholamine and 5hydroxytryptamine biosynthesis in brainstem catecholaminergic cell groups and in the hypothalamus (Soulage et al, 2004;Berenguer et al, 2003a). The prevalence of toluene-related neurotoxicity among workers exposed to toluene is still unclear because of controversial data on neurotoxicity arising from lowdose chronic toluene exposure (<50 ppm; Eller et al, 1999;Gericke et al, 2001;Juntunen et al, 1985;Murata et al, 1994;Seeber et al, 2004;Zupanic et al, 2002).…”
Section: Introductionmentioning
confidence: 99%